Cradle of Conservation - Judd, Richard (Maine Policy Review, 2023)
Conservation history brings to mind epic battles over national parks, free-flowing rivers, and immense wilderness areas in the West. We should not overlook similar accomplishments in the East, however, where citizens and public officials pioneered the conservation movement well before John Muir, Gifford Pinchot, and Theodore Roosevelt coined the term. Maine stands as an example. Not only did it establish its conservation credentials early but it also did so under complicated conditions.